BUDIDAYA TANAMAN MAHONI (Sweitenia macrophylla) DAN PEMANFAATANNYA SEBAGAI TANAMAN OBAT - AA Komang Suardana (JURNAL SEWAKA BHAKTI, 2018)
Batukau Mount with its dense forest as the lungs of Tabanan Regency. As a buffer zone, water sources can irrigate existing subak, one of them is Jatiluwih Subak which is a World Cultural Heritage. At the south foothill of Mount Batukau Mount there is Sad Kahyangan Temple, Batukau Temple. Nature preservation around the temple is still maintained, but over time there are areas that need to be greened. Based on this situation, community service around Batukau Temple is carried out with the theme "Mahogany Cultivation (Sweitenia macrophylla) and Its Use as Medicinal Plants". The community service method was carried out with a lecture system to several community members in Batukau Temple. Conclusions obtained in the cultivation of mahogany plants that need to be considered are hatcheries and nurseries, planting and maintenance. As a medicinal plant, mahogany seed extract can be used as an environmentally friendly vegetable pesticide to control Plutella xylostella and Crosidolomia binolalis in cabbage when pests were in the larval stage and seeds of mahogany fruit contain various substances including flavonoids and saponins that function as bacteriocytes. Key Word : cultivation, Mahogany plant, medicinal plants